2010
DOI: 10.1002/app.32031
|View full text |Cite
|
Sign up to set email alerts
|

One‐step synthesis of triarm block copolymers via simultaneous reversible‐addition fragmentation chain transfer and ring‐opening polymerization

Abstract: One‐step synthesis of star copolymers by reversible addition–fragmentation chain transfer (RAFT) and ring‐opening polymerization (ROP) by using a novel dual initiator is reported. Triarm block copolymers comprising one polystyrene (or polyacrylamide) arm and two poly(β‐butyrolactone) arms were synthesized in one‐step by simultaneous RAFT polymerization of styrene (St) (or acrylamide, designated as AAm) and ROP of β‐butyrolactone (BL) in the presence of a novel trifunctional initiator, 1,2‐propanediol ethyl xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 115 publications
2
8
0
2
Order By: Relevance
“…Hence, it may be expected that they have shorter poly(2-vinylpyridine) segments, which is confirmed by a decrease in the molecular weights of the graft copolymers, as shown in Table 1. The same situation was also observed in our previous articles (58)(59)(60). Increasing the amount of monomers also generally causes an increase in both the yield and the molecular weights of the copolymers as expected.…”
Section: Synthesis Of Poly(vinyl Chloride-graft-2-vinylpyridine) Grafsupporting
confidence: 78%
See 1 more Smart Citation
“…Hence, it may be expected that they have shorter poly(2-vinylpyridine) segments, which is confirmed by a decrease in the molecular weights of the graft copolymers, as shown in Table 1. The same situation was also observed in our previous articles (58)(59)(60). Increasing the amount of monomers also generally causes an increase in both the yield and the molecular weights of the copolymers as expected.…”
Section: Synthesis Of Poly(vinyl Chloride-graft-2-vinylpyridine) Grafsupporting
confidence: 78%
“…Polymers of a well-defined structure and molecular weight can be synthesized by controlled radical-polymerization methods, such as nitroxide-mediated polymerization (37,38), atom-transfer radical polymerization (25,(39)(40)(41)(42)(43)(44), and reversible addition-fragmentation chain transfer (RAFT) polymerization (33,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). RAFT polymerization is one of the most recently developed controlled radical-polymerization methods and is an important technique for the synthesis of copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the research on poly (N‐isopropylacrylamide) (PNIPAM) block copolymer is more systematic and in‐depth . However, due to its poor biocompatibility and low LCST, it has seriously affected its future application prospects. Recent studies have shown that the biocompatibility of poly ( N N ‐diethylacrylamide) (PDEA) is far superior to that of PNIPAM, and its LCST is also higher than that of PNIPAM.…”
Section: Introductionmentioning
confidence: 99%
“…42 Meanwhile, the research on poly (N-isopropylacrylamide) (PNIPAM) block copolymer is more systematic and in-depth. [43][44][45] However, due to its poor biocompatibility and low LCST, [46][47][48] it has seriously affected its future application prospects.…”
mentioning
confidence: 99%
“…"Click" chemistry applications have been available until now [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Macromolecules are used in technological applications and theoretical studies [16][17][18][19][20][21]. Polymers based on polyethylene glycol (PEG) are attractive materials for biomedical, industrial, and chemicals applications, as PEG has unparalleled characters such as superior ion absorbability, flexibility, hydrophilicity, and biocompatibility [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%